Elective Generator Replacement of the Subcutaneous Implantable Defibrillator—Always a Simple Pit Stop? - Fastenrath, Fabian; Wuerfel, Sara; Liebe, Volker; Akin, Ibrahim; Duerschmied, Daniel; Borggrefe, Martin; Kuschyk, Juergen; Rudic, Boris (Journal of Cardiovascular Electrophysiology, 2025)
Background and Aims: The safety and efficacy of the subcutaneous implantable cardioverter‐defibrillator (S‐ICD) has been proven in various clinical trials. Data on device replacement strategies is scarce. This study aims to evaluate long‐term shock efficacy, trends in shock impedance, and the effects of a replacement strategy at elective device replacement. Methods: Between January 2018 and November 2022, a total of 99 consecutive patients underwent S‐ICD device replacement. Shock impedance was determined at initial implantation, before and after device replacement. In case of high shock impedance, additional optimization of lead and generator position was performed if applicable, as well as the removal of fibrous encapsulation ("capsulectomy") of the S‐ICD pocket. Results: Defibrillation testing with the first 65 J shock was successful in 87% of patients after initial device implantation versus 85% with the same device immediately before device replacement (p = 0.88). Eight patients preoperatively failed defibrillation testing with 65 J and 80 J. After a mean dwell time of 65 ± 21 months, shock impedance increased significantly from 82 ± 23 Ω at initial implantation to 98 ± 37 Ω at replacement (p = 0.004). Capsulectomy and optimized repositioning of the S‐ICD lead and generator resulted in a significant decrease of shock impedance to 81 ± 25 Ω as compared to 98 ± 37 Ω before the replacement (p = 0.004). 65 J shock efficacy improved to 95%. Postoperative defibrillation testing was successful in all patients. No acute complications were observed. Conclusion: High conversion rates at device replacement are achievable through optimized replacement strategy. In addition to improving the lead and generator position, capsulectomy appears to be a safe and effective way to reduce shock impedance and might contribute to overall system performance.